Learning to love ourselves again: Organizing Filipinx/a/o scholar-activists as antiracist public health praxis - Manalo-Pedro, Erin; Mackey, Andrea; Banawa, Rachel A.; Apostol, Neille John L.; Aguiling, Warren; Aguilar, Arleah; Oronce, Carlos Irwin A.; Sabado-Liwag, Melanie D.; Yee, Megan D.; Taggueg, Roy; Bacong, Adrian M.; Ponce, Ninez A. (Frontiers in Public Health, 2022)
A critical component for health equity lies in the inclusion of structurally excluded voices, such as Filipina/x/o Americans (FilAms). Because FilAm invisibility is normalized, denaturalizing these conditions requires reimagining power relations regarding whose experiences are documented, whose perspectives are legitimized, and whose strategies are supported. In this community case study, we describe our efforts to organize a multidisciplinary, multigenerational, community-driven collaboration for FilAm community wellness. Catalyzed by the disproportionate burden of deaths among FilAm healthcare workers at the onset of the COVID-19 pandemic and the accompanying silence from mainstream public health leaders, we formed the Filipinx/a/o Community Health Association (FilCHA). FilCHA is a counterspace where students, faculty, clinicians, and community leaders across the nation could collectively organize to resist our erasure. By building a virtual, intellectual community that centers our voices, FilCHA shifts power through partnerships in which people who directly experience the conditions that cause inequities have leadership roles and avenues to share their perspectives. We used Pinayism to guide our study of FilCHA, not just for the current crisis State-side, but through a multigenerational, transnational understanding of what knowledges have been taken from us and our ancestors. By naming our collective pain, building a counterspace for love of the community, and generating reflections for our communities, we work toward shared liberation. Harnessing the collective power of researchers as truth seekers and organizers as community builders in affirming spaces for holistic community well-being is love in action. This moment demands that we explicitly name love as essential to antiracist public health praxis.